Pengaruh Terapi Murottal Al – Qur’an terhadap Tingkat Kecemasan Ibu Hamil Trimester III dalam Menghadapi Proses Persalinan - Rahmadhani, Ayu; Agustini, Tutik; Taqiyah, Yusrah (Pusat Kajian dan Pengelola Jurnal Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2021)
Pregnancy is a period of female reproduction that requires physical and psychological adaptation. The psychological reactions in pregnancy that occur are anxiety reactions, this disorder is characterized by anxiety and excessive need. Murottal Al-Qur'an therapy has an effect on reducing anxiety levels. The purpose of this study was to determine the effect of murottal Al-Qur'an therapy on the anxiety level of third trimester pregnant women in facing the labor process. This research was conducted at the Kolakaasi Puskesmas, Kolaka Regency, using a quasi-experimental design. As for the research design used was One Group Pretest-Postest Design. The sampling technique used a total sampling of 20 third trimester pregnant women who experience anxiety. The data analysis used was univariate and bivariate, where the bivariate used Wilcoxon test analysis. The instrument used was the Hamilton Rating Scale for Anxiety (Hars). The results of this study indicate that there is an effect of Murottal Al - Qur'an therapy on the level of anxiety in pregnant women (Ï = 0.000) where there are differences in the results before and after giving Murottal Al - Qur'an therapy on the level of anxiety in third trimester pregnant women in facing the process of breeding at Puskesmas Kolakaasi, Kolaka Regency. The conclusion of this study is that there is an effect of murottal Al-Qur'an therapy on the anxiety level of third trimester pregnant women in facing the labor process. Therefore, it is hoped that in overcoming anxiety before childbirth, you can apply relaxation techniques with murottal Al-Qur'an therapy without directly consuming pharmacological drugs, then this research can also be additional information, especially related to maternity nursing science.